1998
DOI: 10.1006/anbo.1998.0628
|View full text |Cite
|
Sign up to set email alerts
|

Embryology ofCymbidium sinense:the Microtubule Organization of Early Embryos

Abstract: In Cymbidium sinense, the pattern of embryo development is unusual in that oblique cell divisions result in the formation of several suspensor cells prior to the development of the embryo proper. Characteristic changes in microtubular distribution can be found within the zygote and the proembryo during their development. After fertilization, the ellipsoid-shaped zygote has randomly distributed microtubules within its cytoplasm. As the zygote takes on a more rounded appearance, microtubules organize into a dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…The described configurations of the cytoskeleton probably are also involved in maintenance of the characteristic shape of the basal cell nucleus. Similar relationships have been observed in angiosperms in the endosperm (Huang et al, 1998), syncytia (Płachno et al, 2010, large polyploid cells such as the embryo suspensor Bohdanowicz, 2007, 2009;Kozieradzka-Kiszkurno et al, 2011) and endosperm haustoria Świerczyńska et al, 2013). Disturbances of radial perinuclear microtubule systems as well as increasing vacuolization of the cell were observed in older suspensor basal cells of G. lutea.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The described configurations of the cytoskeleton probably are also involved in maintenance of the characteristic shape of the basal cell nucleus. Similar relationships have been observed in angiosperms in the endosperm (Huang et al, 1998), syncytia (Płachno et al, 2010, large polyploid cells such as the embryo suspensor Bohdanowicz, 2007, 2009;Kozieradzka-Kiszkurno et al, 2011) and endosperm haustoria Świerczyńska et al, 2013). Disturbances of radial perinuclear microtubule systems as well as increasing vacuolization of the cell were observed in older suspensor basal cells of G. lutea.…”
Section: Discussionsupporting
confidence: 74%
“…They have shown that the suspensor is actively involved in the uptake and transport of nutrients and regulators from surrounding tissues to the embryo proper, and that it is a source of signals or a mediator of signals affecting the course of embryogenesis (Yeung and Clutter, 1979;Bohdanowicz, 1987Bohdanowicz, , 2001). There is not so much published work reporting observations of the cytoplasmic skeleton in differentiating cells of embryo suspensors (Webb and Gunning, 1991;Ye et al, 1997;Huang et al, 1998;Tung et al, 2000), and only a few reports describe the cytoskeleton in highly endopolyploid embryo suspensor cells (e.g., in Alisma plantago-aquatica, Bohdanowicz, 2007, 2009;in Sedum acre, Kozieradzka-Kiszkurno et al, 2011). To understand the role of the cytoskeleton in the development of highly endopolyploid plant cells it is necessary to know the distribution of the actin and tubulin skeleton during the differentiation of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that cytoplasmic skeleton in plant cells plays an important role during growth and differentiation. So far, the organization of cytoskeletal components has been studied mainly during megasporogenesis and megagametogenesis [32][33][34][35][36][37]. On the other hand, little information relates to the cytoskeleton during differentiation of highly polyploid cells of embryonic suspensor.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28] The hardness, tensile stress and total elongation of the present steels are plotted against the tempering temperature in Figs. 1(a), 1(b) and 1(c), respectively.…”
Section: Discussionmentioning
confidence: 99%